Establishing a multidisciplinary initiative for interoperable electronic health record innovations at an academic medical center. Issue 3 (31st July 2021) - Kawamoto, Kensaku; Kukhareva, Polina V; Weir, Charlene; Flynn, Michael C; Nanjo, Claude J; Martin, Douglas K; Warner, Phillip B; Shields, David E; Rodriguez-Loya, Salvador; Bradshaw, Richard L; Cornia, Ryan C; Reese, Thomas J; et al.
Abstract: Objective: To establish an enterprise initiative for improving health and health care through interoperable electronic health record (EHR) innovations. Materials and Methods: We developed a unifying mission and vision, established multidisciplinary governance, and formulated a strategic plan. Key elements of our strategy include establishing a world-class team; creating shared infrastructure to support individual innovations; developing and implementing innovations with high anticipated impact and a clear path to adoption; incorporating best practices such as the use of Fast Healthcare Interoperability Resources (FHIR) and related interoperability standards; and maximizing synergies across research and operations and with partner organizations. Results: University of Utah Health launched the ReImagine EHR initiative in 2016. Supportive infrastructure developed by the initiative include various FHIR-related tooling and a systematic evaluation framework. More than 10 EHR-integrated digital innovations have been implemented to support preventive care, shared decision-making, chronic disease management, and acute clinical care. Initial evaluations of these innovations have demonstrated positive impact on user satisfaction, provider efficiency, and compliance with evidence-based guidelines. Return on investment has included improvements in care; over 35 million in external grant funding; commercial opportunities; and increased ability to adapt to a changing healthcare landscape. Discussion: Key lessons learned include the value of investing in digital innovation initiatives leveraging FHIR; the importance of supportive infrastructure for accelerating innovation; and the critical role of user-centered design, implementation science, and evaluation. Conclusion: EHR-integrated digital innovation initiatives can be key assets for enhancing the EHR user experience, improving patient care, and reducing provider burnout.